Exploring Health Care Disparities in Genetic Testing and Research for Hereditary Cardiomyopathy: Current State and Future Perspectives - Huang, Helen; Verma, Jay; Mok, Valerie; Bharadwaj, Hareesha R.; Alrawashdeh, Maen M.; Aratikatla, Adarsh; Sudan, Sourav; Talukder, Suprateeka; Habaka, Minatoullah; Tse, Gary; Bardhan, Mainak (Global Medical Genetics, 2024)
Background Hereditary cardiomyopathies are commonly occurring myocardial conditions affecting heart structure and function with a genetic or familial association, but the etiology is often unknown. Cardiomyopathies are linked to significant mortality, requiring robust risk stratification with genetic testing and early diagnosis.Hypothesis We hypothesized that health care disparities exist in genetic testing for hereditary cardiomyopathies within clinical practice and research studies.Methods In a narrative fashion, we conducted a literature search with online databases such as PubMed/MEDLINE, Google Scholar, EMBASE, and Science Direct on papers related to hereditary cardiomyopathies. A comprehensive analysis of findings from articles in English on disparities in diagnostics and treatment was grouped into four categories.Results Racial and ethnic disparities in research study enrollment and health care delivery favor White populations and higher socioeconomic status, resulting in differences in the development and implementation of effective genetic screening. Such disparities have shown to be detrimental, as minorities often suffer from disease progression to heart failure and sudden cardiac death. Barriers related to clinical genetic testing included insurance-related issues and health illiteracy. The underrepresentation of minority populations extends to research methodologies, as testing in ethnic minorities resulted in a significantly lower detection rate and diagnostic yield, as well as a higher likelihood of misclassification of variants.Conclusions Prioritizing minority-based participatory research programs and screening protocols can address systemic disparities. Diversifying research studies can improve risk stratification strategies and impact clinical practice.
Keywords: hereditary cardiomyopathy; disparities; genetic testing; diversity; ethnic representation